Profile of Ofatumumab in the Treatment of Multiple Sclerosis: Design, Development and Place in Therapy - Awada Z; Hameed N; Harel A (Drug Design, Development and Therapy)
Zeinab Awada,1 Natasha Hameed,2 Asaff Harel1,2 1Northwell Comprehensive Multiple Sclerosis Center, Department of Neurology, Lenox Hill Hospital/Donald and Barbara Zucker School of Medicine at Hofstra, New York, NY, USA; 2Northwell Comprehensive Multiple Sclerosis Center, Department of Neurology, Long Island Jewish Medical Center/ North Shore University Hospital/ Donald and Barbara Zucker School of Medicine at Hofstra, New York, NY, USACorrespondence: Asaff Harel, Northwell Comprehensive Multiple Sclerosis Center, Department of Neurology, Lenox Hill Hospital/Donald and Barbara Zucker School of Medicine at Hofstra, 130 East 77th Street, New York, NY, 10075, USA, Tel +1 401-323-2210, Fax +1 212-434-2279, Email aharel@northwell.eduAbstract: Targeting B cells through monoclonal antibodies against CD20 has emerged as a highly effective strategy in managing disease activity in patients with relapsing forms of multiple sclerosis. This efficacy was initially demonstrated with rituximab and further affirmed with ocrelizumab. Ofatumumab is the first fully human IgG1 monoclonal antibody (mAb) approved for the treatment of MS. It is characterized by its convenient self-administered regimen of once-monthly subcutaneous injections. Its human antibody nature contributes to a significantly lower risk of immunogenicity compared to rituximab. Clinical trials have consistently shown its effectiveness in significantly reducing annualized relapse rates, MRI-detected lesion activity, and disability progression when compared to teriflunomide, a standard therapy for MS. Additionally, ofatumumab exhibits a manageable tolerability profile, with adverse events primarily comprising infections and injection-related reactions. This review describes ofatumumab pharmacology, core clinical trial data and clinical efficacy in addition to safety issues.Keywords: ofatumumab, multiple sclerosis, relapsing remitting multiple sclerosis, anti- CD20 monoclonal antibodies, disease modifying therapeutics, safety